Instytucja Marszałka Seniora Sejmu w polskim porządku prawnym - Maroń, Grzegorz (Polityka i Społeczeństwo, 2021)
The Senior Marshal is an honorary and ephemeral post in the Sejm of the Republic of Poland. The given institution dates back to 1919 and the Legislative Sejm in the Second Polish Republic. The Senior Marshal is appointed by the President from amongst the elder Deputies. There are three main competences of the Senior Marshal. He opens the first sitting of a newly elected Sejm, which is accompanied by the striking of the Marshal’s mace three times against the floor. Next he conducts the procedure of taking the oath of office of the Deputies. Finally he conducts the election of the Marshal of the Sejm. The last two functions the Senior Marshal performs with assistance of temporary secretaries appointed by him from amongst the youngest Deputies in such number as may be necessary to discharge such functions. The moment of taking the chair during the first sitting by newly elected Marshal of the Sejm terminates the parliamentary activity of the Senior Marshal in a given term of office of the Sejm.